IMRT and carbon ion boost for malignant salivary gland tumors: interim analysis of the COSMIC trial - Jensen, Alexandra; Nikoghosyan, Anna; Lossner, Karen; Herfarth, Klaus; Debus, Jürgen; Münter, Marc (BMC cancer, 2012)
The COSMIC trial is designed to evaluate toxicity in dose-escalated treatment with intensity-modulated radiotherapy (IMRT) and carbon ion boost for malignant salivary gland tumors (MSGT) of the head and neck including patients with inoperable/ incompletely resected MSGTs (R2-group) and completely resected tumors plus involved margins or perineural spread (R1-group).